The Impact of the Bank of Japan's Low-Interest Rate Policy on the Japanese Banking Sector - Juliane Gerstenberger; Gunther Schnabl (Credit and Capital Markets – Kredit und Kapital, 2021)
This paper presents an analysis of the impact of the Bank of Japan's low-interest rate policy on the banking sector in the wake of the 1998 Japanese financial crisis. We show how the low-cost liquidity provision as a means to stabilize banks has created a growing gap between deposits and loans in the financial system and how the low-interest rate policy has compressed interest margins as the traditional source of banks' income. Efficiency scores are compiled to estimate the effect of the Bank of Japan's monetary policy on banks' technical efficiency. The estimation results provide evidence that the Japanese monetary policy has contributed to declining efficiency in the banking sector, despite~– or possibly because of~– the increasing concentration within this sector.
Keywords: E52; E58; F42; E63; 330; Japan; Monetary Policy; Crisis Management; Banking Sector; City Banks; Regional Banks; Shinkin Banks; Concentration